Pengaruh Employee Resilience Terhadap Organizational Citizenship Behavior yang di Mediasi Oleh Organizational Commitment di Pangeran Beach Hotel Padang - Mutiara Fitri; Feri Ferdian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research begins with the discovery of problems related to the low resilience of employees in dealing with work pressure in the Pangeran Beach Hotel Padang environment. This study aims to analyze the effect of employee resilience on organizational citizenship behavior mediated by organizational commitment at Pangeran Beach Hotel Padang. The research population was 110 employees of Pangeran Beach Hotel Padang with purposive sampling method obtained a sample of 86 respondents. The data analysis method uses descriptive statistical tests and SmartPLS 3.0. The results of the research seen from direct hypothesis testing employee resilience has a positive and significant effect on OCB with a statistical t value of 3.947, employee resilience has a positive and significant effect on organizational commitment with a statistical t value of 3.938, organizational commitment has a positive and significant effect on OCB with a statistical t value of 2.751, and indirect results employee resilience has no significant effect on OCB through organizational commitment with a statistical t value of 1.700 which is smaller than 1.96.